Executive Committee Minutes 2013-09-19 - Academic Senate:::::::::
Agenda approved. Minutes of 9/5/13 approved. Chair Report. Math/Stats Program Revision approved for Senate's consent calendar. CFA Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. APC Report. EPC Report. FSAC Report. SAC Report. Associated Students Report. Ex Com Rep to Sustainability Ex Com Report. Senate agenda approved.